OP0144 The Effect of TNF Inhibition on Radiographic Progression in Ankylosing Spondylitis: An Observational Cohort Study of 384 Patients. (9th June 2015) - Maksymowych, W.P.; Zheng, Y.; Wichuk, S.; Chiowchanwisawakit, P.; Lambert, R.G.
Abstract : Background: Comparisons of radiographic progression over 2 years between AS patients receiving anti-TNF therapies in open label extensions of phase III trials and a historical cohort have not demonstrated any impact of treatment. An analysis of radiographic progression in an observational cohort using a propensity matching technique has shown that anti-TNF therapy ameliorates radiographic progression, especially when treatment is introduced within 5 years of disease onset 1 . Objectives: To assess the impact of anti-TNF therapy on radiographic progression in an observational cohort of patients using propensity matching. Methods: In the FOllow-up Research Cohort in AS (FORCAST), 384 patients with AS from Northern Alberta attending community and academic rheumatology practices have been assessed over a mean (SD) follow up of 3.3 (1.7) years for clinical and laboratory outcomes every 6 months, and had spinal radiography at baseline and at follow up (mean (SD) (interval between first and last radiographs 2.9 (1.3) years). Patients received standard therapy (n=148) or anti-TNF (n=236). Radiographs were scored by two readers using the mSASSS with adjudication by a third reader according to prespecified rules. The impact of anti-TNF was assessed using univariate and multivariate Tobit regression. Propensity matching was based on a caliper of 0.1 in a logistic model using pre-treatment BASDAI, mSASSS, CRP, sex, age, NSAID use (yes/no), smoking, and disease duration. Multiple propensity score analysis based on multinomial logistic regression was used to compare groups according to disease duration before start of anti-TNF. Results: There were (287 and 74.7%) males of mean (SD) age was 45.4 (12.1) years, mean (SD) disease duration 21.4 (11.7) years, mean (SD) baseline mSASSS of 17.2 (18.4), and mean (SD) progression of 1.0 (1.3) mSASSS units. In univariate analyses, significant predictors of progression were baseline mSASSS (p<0.001), ASDAS (p=0.025), male sex (p=0.026), age (p=0.001), and disease duration (p=0.003), and CRP at post-treatment of <6mg/L (p=0.024). Smoking, B27, NSAIDs, anti-TNF therapy (yes/no), duration of anti-TNF therapy, proportion of disease duration exposed to anti-TNF, were non-significant. In multivariable Tobit regression, only baseline mSASSS was a significant predictor (p=0.014). After propensity matching, 226 patients could be included in the post-match analysis. In the final multivariable Tobit model, only baseline mSASSS was a significant predictor (p=0.022). Multiple propensity score adjusted analysis demonstrated significantly less radiographic progression in patients who received anti-TNF within 5 years of disease onset (n=15) when compared to those receiving treatment after >10 years of disease (n=178) or on standard therapy (p=0.01 for both). Conclusions: Anti-TNF therapy demonstrated no effect on radiographic progression in this observational cohort. Early treatment may be a factor in reducing progression although only a small proportion of patients receive early intervention with anti-TNF in routine practice. References: Haroon et al. Arthritis Rheum 2013; 65: 2645-2654 Disclosure of Interest: W. Maksymowych Consultant for: Abbvie, Amgen, Eli-Lilly, Janssen, Merck, Pfizer, UCB, Y. Zheng: None declared, S. Wichuk: None declared, P. Chiowchanwisawakit: None declared, R. Lambert Consultant for: Abbvie